A New Transportation Ministry School System Through Virtual Classroom To Maximize The Communications Technology System And Minimize The Empty Class During Covid-19 - Hartanto, Hartanto (IWTJ : International Water Transport Journal, 2020)
Virtual Classroom is a new term and innovation in the current teaching trends and developments in the education especially in the maritime school use communications systems, computers, Information Technology (IT) and telecommunications, particularly satellite communications. And also now, we got the pandemy of Covid-19 its impact to the learning system. It explored some of the current distance learning methodologies and the associated technologies used in their way to transfer the knowledge from the teacher and the students, especially the class which frequently empty because the teachers still in their duty especially happened in Ministry of Transportation who the teacher or trainer have to work, meeting, visiting, etc. This new approach to solve the current dilemma the country is facing now. That is, meeting both the qualitative requirements of IMO/STCW’95 and satisfying the quantitative demands of the shipping industry to avert a potential international manning crisis. The purpose of this paper is be the innovation tool to maximize the communications technology system and minimize the empty class during Covid-19 in the maritime school and assessing the technical feasibility of establishing a Distance Learning Programme for the candidate of seafarers in the Ministry of Transportation School area. The study endeavoured to make a detailed cost estimate of the resources necessary such as financial, material, human and other resources in establishing and running such a programme. Finally, it recommended the establishment of a new system in Distance Learning Programme through Virtual Classroom and to be the recommendations to all the Ministry of Transportation School to improve the quality of their education in the case of transfer knowledge and prepare the qualified seafarers. Keywords: Innovation; Virtual Classroom; Communications; Technology; Covid-19.